The Influence of Religiosity and Transparency on Production Factors of Sharecrops and Sharecropping Contract in East Java - Suyoto Arief; Adib Susilo; Achmad Fajaruddin (Department of Islamic Economics, IPB University, 2022)
This paper seeks the relations between the religiosity and the transparency to the production factors usage in the land crops cultivation as well as the effect of production factor to the sharecropping contract in East Java. The method employs in this study is Structural Equation Modelling (SEM) with the respondent of the research is 400 farmers from the 8 counties in East Java. The result shows that religiosity and transparency have positives and significant effect to the production factors usage in the cultivation of the land crops in East Java with the p-value respectively 0.008 for religiosity to production factors and 0.001 for transparency to production factors. Meanwhile, the influence of production factors to the sharecropping contract is positive and significant with p-value about 0.001. Furthermore, the R-square of production factors is about 0.907 which mean 90.7% of production factors variable is explained by religiosity and transparency variables while the rest of it is explained by other variables out of this research. Meanwhile, the sharecropping contracts R-square is about 0.629 which means 62.9% of sharecropping contracts variable is explained by production factors variable while the rest of it about 37.1% is explained by other variables out of this research.